Test of The Effectiveness of Trigona Madu (Trigona sp.) on Healing of Burns and Leukosit LevelsIn White Rats (Rattus norvegicus) - Fitrah Glora Sukma; Nasrudin Andi Mappaware; Andi Dhedie Prasatia Sam; Moch Erwin Rachman; Ekawati Mulyadi (Poltekkes Kemenkes Surabaya, 2025)
Burn injuries are complex conditions requiring effective treatment to accelerate healing and minimize complications. This study investigates the therapeutic potential of Trigona honey (Trigona sp.) in healing second-degree burn wounds and its effect on leukocyte levels in white rats (Rattus norvegicus). Using a true experimental design with a posttest control group, 24 male rats were divided into four groups: negative control (distilled water), positive control (povidone iodine), and two treatment groups receiving topical Trigona honey once or twice daily. Burn wound size was measured on days 1, 7, and 14 using a caliper, while leukocyte levels were assessed on day 7 using the improved Neubauer counting chamber. Data were analyzed with SPSS, employing normality tests, one-way ANOVA, and Repeated ANOVA tests as appropriate. Results indicated significant wound size reduction in all groups, with the twice-daily Trigona honey group showing the greatest improvement (1.12 cm² reduction after 14 days). However, leukocyte level changes were not statistically significant among groups. The therapeutic effects of Trigona honey are attributed to its bioactive compounds, including flavonoids and phenolics, which enhance re-epithelialization, angiogenesis, and granulation tissue formation. Despite insignificant leukocyte modulation, Trigona honey demonstrated notable efficacy in accelerating wound healing compared to control treatments. Further studies are recommended to optimize dosing, evaluate long-term effects, and conduct clinical trials in humans. Trigona honey holds promise as a natural alternative for burn treatment, particularly when formulated into easily applicable forms such as ointments or gels.